Democratic values and social dialogue : issues and analysis in contemporary Francophone Africa - (:unkn) unknown (My University, 2022)
One of the real challenges for Africa in launching integrated social and economic development in Africa is democracy. Yet the gap between knowledge, theory and democratic life is such that it invites any serious observer to ask where it comes from and how it can be overcome. This requires serious study, in-depth and advanced research. This is why our research on "Democratic values and social dialogue. Issues and analysis of contemporary cases in Francophone Africa" examined the gap between the theoretical model of democracy based on supposedly universal values and the reality, experienced and observed in Africa. While political pressures, both within and outside states, are pushing their leaders to establish rules that are more respectful of democratic values, it remains to be seen how these have been put into practice since the declarations of independence at different levels - from the village to national governments and regional intergovernmental cooperation - to promote greater participation of citizens in power despite the various crises that hamper this process. Social dialogue has provided an exemplary mechanism whose procedure can be summarized as consultation, discussion and negotiation, including forms of mediation and reconciliation. The prospect of a social dialogue open to public action is envisaged to bring together the multifaceted actors around a wide range of issues to be discussed together. In order to remedy the superficiality of the meetings, the African experience of social dialogue must change its software to adapt to the concrete reality. The use of Africa's own resources has its place in mobilizing the values of the African palaver for concrete dialogue, provided that it is also updated and used in a way that guarantees freedom of opinion and collective choice.
Keywords: African Research